PENURUNAN KADAR MATRIKS EKSTRASELULER UTERUS TIKUS DENGAN BERTAMBAHNYA UMUR - Safrida Safrida (Universitas Syiah Kuala, 2011)
This study aims to determine the levels of extracellular matrix (collagen content) at various levels of aged rats and aged rats to acquire suitable for use as an animal model of aging for the reproductive system. Experimental design used was Complete Randomized Design (CRD), which consists of 5 (five) experimental groups, each group consist of three (3) rats, which is the group one used 12 months aged rats (K12), group 2 used 18 months aged rats (K18), group 3 used 24 months aged rats (K24), a group of 4 using 30 months aged rats (K30), groups of 5 using 36 months aged rats (K36). The data obtained were analyzed using Analysis of Variance (ANOVA) followed by Duncan test. Decreased levels of collagen (extracellular matrix) of the uterus begin to occur in rats aged 24 months. An aged rat suitable for use as animal models ofaging for the reproductive system is a 24-36 months aged rats.